Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Itad, Oxfam and IDS, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

Achieving value for money through procurement. Part 2: DFID’s approach to value for money through tendering and contract management - A performance review - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
Summary In 2016-17, the Department for International Development (DFID) spent £1.4 billion, or 14% of its budget, through commercial suppliers on contracts ranging from school construction to family planning services and the delivery of humanitarian aid. The quality of its procurement and contract management – how it engages and manages commercial firms to support the delivery of aid programmes on time, to budget and at the appropriate quality – is a key driver of value for money for UK aid. It is also a subject of considerable Parliamentary and public interest. In recent years, DFID has implemented a range of initiatives to strengthen its procurement practices and embed commercial capability across the department – including its 2017 Supplier Review, undertaken to address concerns about excessive profit-making by DFID suppliers. This review on achieving value for money through procurement (part 2) was published in September 2018. We awarded a green-amber score and made three recommendations to government. The follow-up to this review was published in July 2020, and rated the government’s response as ‘inadequate’, as a result of DFID’s failure to put in place a formal contract management regime, despite the risks this entails for programme results. We will return to this in the next follow-up in summer 2021. Review Our review found an appropriate overall approach to procurement with good performance in most areas of tendering, but significant weaknesses in contract management. We therefore awarded a green-amber score and made three recommendations to government. Findings Since 2015, DFID has progressed towards a more mature procurement approach. DFID’s tender process follows current EU legislation and UK government guidelines and cross-government peer reviews confirm improvements in DFID’s procurement approach. The Supplier Review lent momentum to the reforms but risks having unintended consequences. Poor consultation with suppliers has heightened the risk of unintended consequences. DFID is reviewing its business processes to protect aid recipients from sexual abuse and exploitation. DFID does not always choose the most appropriate procurement process but a new strategic sourcing process has resulted in stronger procurement planning. DFID has built up its commercial capability, but this will need to be an ongoing process. The contract management function in DFID is poorly defined and contracts are frequently amended or extended beyond their advertised length and values. Inception phases are often too short for adequate preparation and planning. Progress on flexible and adaptive programming will require more innovative approaches to tendering and contract management. Recommendations Before the next major revision of its supplier code and contracting terms, or future changes that may materially affect suppliers, DFID should conduct an effective consultation process with its supplier market, to ensure informed decisions and minimise the risks of unintended consequences. DFID should accelerate its timetable for acquiring a suitable management information system for procurement, to ensure that its commercial decisions are informed by data. DFID should instigate a formal contract management regime, underpinned by appropriate training and guidance and supported by a senior official responsible for contract management across the department. The new regime should include appropriate adaptive contract management techniques, to ensure that supplier accountability is balanced with the need for innovation and adaptive management in pursuit of development results.

Decision-Making and Data Use Landscaping [at DFID] - Powell, Josh; Orton-Vipond, Sarah; Bhatia, Vinisha; Kilroy, Annie (Development Gateway, 2018)
As DFID aims to harness the Data Revolution, ensuring that data1 drive decision-making, public accountability, and the achievement of the Sustainable Development Goals (SDGs), ensuring that systems, processes, and skills for data are aligned with these objectives is paramount. Across sector policy teams, country offices, and various analytical and technical cadres, different strengths and weaknesses, as well as needs and ambitions exist. To inform a strategic approach to data, as framed in its forthcoming Data Roadmap, DFID collaborated with Development Gateway to perform a Decision and Data Use Landscaping study. This report details lessons learned from approximately 60 interviews across 4 DFID country offices, all sector policy teams, senior managers, and various analytical and technical cadres and offices.